Blood Leukocyte Ratios as Predictive Markers of Chronic Enteropathy Phenotypes in Cats - Alexandros O. Konstantinidis; Katerina K. Adamama-Moraitou; Ashley Griggs; Margaret L. Musser; Ariel S. Nenninger; Nektarios Soubasis; Dimitra Pardali; Mathios E. Mylonakis; Albert E. Jergens (Veterinary Sciences)
This retrospective study assessed the potential of blood leukocyte ratios as diagnostic biomarkers in cats with chronic enteropathies (CE). Absolute neutrophil-to-lymphocyte (NLR), neutrophil-to-monocyte (NMR), and lymphocyte-to-monocyte (LMR) ratios were calculated from the hematological profiles of 221 cats, including healthy controls (n = 73), and those diagnosed with food-responsive enteropathy (FRE, n = 59), steroid-responsive enteropathy (SRE, n = 56), or small cell lymphoma (SCL, n = 33). SCL cats had higher NLRs than SRE (p = 0.002) and FRE (p = 0.028), and lower LMRs than SRE (p = 0.012) and FRE (p = 0.001). Healthy cats had lower NLRs compared to the FRE (p < 0.001), SRE (p < 0.001), and SCL (p < 0.001) cats and higher LMRs compared to the FRE (p < 0.001), SRE (p < 0.001), and SCL (p < 0.001) cats. Receiver operating characteristic (ROC) curve analysis demonstrated that NLR ≥ 11.6 differentiated SCL from SRE with 87.5% specificity but low sensitivity (39.4%). NMR ≥ 34.5 distinguished FRE from SRE with 52.5% sensitivity and 69.6% specificity. LMR ≥ 3.72 differentiated SRE from SCL with 67.9% sensitivity and 60.6% specificity. Although significant differences in leukocyte ratios were observed among groups, their diagnostic accuracy in differentiating CE phenotypes was suboptimal. These findings suggest that the utility of NLR, NMR, and LMR as standalone diagnostic tools is limited.